2012
DOI: 10.19030/ajbe.v5i3.6998
|View full text |Cite
|
Sign up to set email alerts
|

Educational Context: Preparing Accounting Students To Identify Ethical Dilemmas

Abstract: We examine the effect of different contexts in an educational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
10
1
1
Order By: Relevance
“…More specifically, the findings concur with scholars (Eweje and Brunton, 2010;Boateng and Agyapong, 2017) who found no significant difference in the ethical sensitivity of male and female business and accounting students. However, the findings contradict some previous studies (Simga-Mugan et al, 2005;Billiot et al, 2012;Ogungbamila and Udegbe, 2014;Kennedy et al, 2017;Cheah and Shimul, 2020;Valente et al, 2021) which contend that females are more ethically sensitive than males. But, this also contradicts Zopiatis and Krambia-Kapardis (2007) who found that male students in Cyprus tend to exhibit more ethical sensitivity to computer related ethics and selfishness Cynicism and ethical sensitivity compared to females.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…More specifically, the findings concur with scholars (Eweje and Brunton, 2010;Boateng and Agyapong, 2017) who found no significant difference in the ethical sensitivity of male and female business and accounting students. However, the findings contradict some previous studies (Simga-Mugan et al, 2005;Billiot et al, 2012;Ogungbamila and Udegbe, 2014;Kennedy et al, 2017;Cheah and Shimul, 2020;Valente et al, 2021) which contend that females are more ethically sensitive than males. But, this also contradicts Zopiatis and Krambia-Kapardis (2007) who found that male students in Cyprus tend to exhibit more ethical sensitivity to computer related ethics and selfishness Cynicism and ethical sensitivity compared to females.…”
Section: Discussioncontrasting
confidence: 99%
“…It was also established that male students are more cynical and unethical than female students. Similarly, Billiot et al (2012) discovered that females were more ethically sensitive than males regardless of age or ethics courses. Several other scholars in different geographical contexts contend that females have higher ethical sensitivity than males (Cohen, et al , 2001; Sidani et al , 2009; Ogungbamila and Udegbe, 2014).…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%
“…The factors elevating moral reasoning and development has drawn attention from many researchers (Billiot et al, 2012;Brown-Liburd & Porco, 2011;D. M. Fleming, Lightner, & Romanus, 2009;Fourie & Contogiannis, 2014).…”
Section: Moral Reasoning Development and Capabilitymentioning
confidence: 99%
“…Hasil ini membuktikan bahwa pendidikanetika yang diajarkan dalam program akuntansi memiliki dampak positif terhadap peningkatan kemampuan mahasiswa akuntansi dalam menyadari suatu masalah etika dengan asumsi semester 6 dan 8 lebih banyak menerima pendidikan etika akuntansi dibandingkan semester 2 dan 4. Hasil ini konsisten dengan penelitian Billiot et al (2012), Lau (2010), Cabe K (2013), Chan & Leung (2006), LaGrone et al (1996, Saat et al (2010b), dan Tailor (2013), yang menyatakan bahwa pemberian pelatihan etika yang benar mampu meningkatkan sensitivitas etis mahasiswa akuntansi dan membuktikan bahwa mahasiswa yang telah mengikuti pendidikan etika lebih tinggi sensitivitas etisnya dibandingkan mahasiswa yang belum pernah mengikuti pelatihan etika.…”
Section: Pengujian Hipotesis 1aunclassified